Wildfires and precipitation in the lowlands of Guatemala: an analysis of precipitation and vegetation indices as potential wildfire drivers - Malaker, Tanmoy, author; Leisz, Stephen J., advisor; Pons, Diego, committee member; Stevens-Rumann, Camille, committee member (Colorado State University. Libraries, 2023)
Wildfire is an inevitable natural disaster that is considered exclusive to dry and temperate regions. However, the increasing wildfire occurrences in tropical and humid forest regions urge us to investigate the drivers of this natural phenomenon for a humid forest region. Although wildfire is inevitable, it can be managed with proper strategies; thus, identifying the drivers of wildfire in humid and tropical regions is imperative. This thesis focuses on identifying the role of precipitation as a driver for wildfire occurrences and fuel generation for fires in a humid forest ecological system in the lowlands of Guatemala (Petén). Using the data library and cloud computation system of the International Research Institute for Climate and Society (IRI), INAB (Instituto Nacional de Bosques/Guatemala's Forest Authority) fire records for Guatemala, and geospatial tools like GIS and Google Earth Engine, the thesis identifies the influence of precipitation on vegetation and wildfires in Petén. The findings suggest that precipitation's influence on Petén's wildfires is two-dimensional. Precipitation influences vegetation or total fuel generation and fire occurrences by influencing fuel availability by influencing green-up and the dry down of fuels in a humid forest ecosystem. This two-dimensional influence makes precipitation one of the most critical drivers of wildfire for tropical-humid forest ecology. Besides the seasonal accumulative precipitation, the precipitation pattern and amount at different times within a preceding season of the fire months highly influence vegetation conditions and fire frequencies. The findings also suggest that seasonal precipitation forecasting could potentially be a tool for wildfire management and forecasting.
Keywords: vegetation; precipitation; wildfire